Biophysical Studies of Biomimetic Bone Cement with Alginate for Applications in the Biomedical Field - Al-Harthi, Jamilah Abed (Journal of medical and pharmaceutical sciences, 2022)
Osteoporosis and many other bone defects are described as the diseases that have attracted attention in the past two decades over worldwide. Because of it is known as a silent disease and with a high commonness rate among the elderly, the battle could be difficult. This paper aims to assess the impact of the inclusion of some additions to the brushite cement and use fluid simulation in the body that contain calcium and free of protein in the laboratory as a stimulant for the apatite formed such as bone apatite samples consisting of brushite cement and various elements that have been added to the roofs. The research paper adopted the experimental approach. The stable phases of calcium phosphate cements depend significantly upon temperatures and the presence of water, either during processing or in the use situation. At body temperature, only two calcium phosphates are stable when in interaction with aqueous media such as body fluids. The samples under investigation are used to select samples which can be considered suitable as a biomaterial in vitro. The samples prepared in the form of two samples each one regards with a group of additives including sodium Alginate, Wollastonite, Titanium Oxide, Hydroxyapatite and Zinc Oxide. Soaking brushite samples with their additives in simulated body fluid for one week may cause presence of a bone-like apatite layer phase (Ca10(OH)2(PO4)6, HA) on the surface of these samples. To sustain the aim of the study, the samples studied by using the X-ray diffraction spectra, scanning electron microscope and Raman spectroscopy. The X-ray diffraction used to ensure the presence of the components used in the preparation of the samples is present in the samples or not. The study of X-ray examination for the samples under investigation after soaking for one week in SBF to help us to recognize new phases appearing after the interaction between the samples surfaces and the components of the SBF.
Keywords: Biophysical; Biomimetic Bone; Alginate; Biomedical field; Biomaterials; Brushite; Hydroxyapatite; Sodium Alginate; Wollastonite